2016
DOI: 10.1089/scd.2016.0099
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Differentiation Tendency Toward Hepatocytes from Gene Expression in Undifferentiated Human Pluripotent Stem Cells

Abstract: Functional hepatocytes derived from human pluripotent stem cells (hPSCs) have potential as tools for predicting drug-induced hepatotoxicity in the early phases of drug development. However, the propensity of hPSC lines to differentiate into specific lineages is reported to differ. The ability to predict low propensity of hPSCs to differentiate into hepatocytes would facilitate the selection of useful hPSC clones and substantially accelerate development of hPSC-derived hepatocytes for pharmaceutical research. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…To the best of our knowledge, this is the first report on a human pluripotent stem cell (hPSC) line that is not only showing differentiation impairment, but also specification to the wrong lineage when submitted to well-established differentiation cues. Several groups have reported that the expression levels of specific genes may modulate the propensity of a line to a specific lineage, but in none of these cases the lines committed to a completely different lineage (Jiang et al, 2013a;Kim et al, 2011;Mo et al, 2015;Ran et al, 2013;Yanagihara et al, 2016). Here, we find that WNT and BMP4 activation, along with TGF-β activation by Activin A results in trophoblast-like cell formation.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first report on a human pluripotent stem cell (hPSC) line that is not only showing differentiation impairment, but also specification to the wrong lineage when submitted to well-established differentiation cues. Several groups have reported that the expression levels of specific genes may modulate the propensity of a line to a specific lineage, but in none of these cases the lines committed to a completely different lineage (Jiang et al, 2013a;Kim et al, 2011;Mo et al, 2015;Ran et al, 2013;Yanagihara et al, 2016). Here, we find that WNT and BMP4 activation, along with TGF-β activation by Activin A results in trophoblast-like cell formation.…”
Section: Discussionmentioning
confidence: 45%
“…Additionally, expression levels of miR-371-3 and other non-coding RNAs have been linked to decreased neuroectoderm differentiation efficiency (Kim et al, 2011;Mo et al, 2015), and WNT3 levels are positively correlating with definitive endoderm commitment (Jiang et al, 2013a). Lastly, RUNX1A affects hematopoietic lineage formation (Ran et al, 2013) and bFGF-1, RHOU and TYMP are associated with low hepatic differentiation efficiency (Yanagihara et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our study also confirmed these findings, and we found that iPSC lines that expressed higher levels of SALL3 on day 7 of EB formation showed greater potential for melanocyte differentiation[ 15 ]. Additionally, miR-371-3 plays both a predictive and functional role in neurogenic differentiation[ 16 ], and the low expression of fibroblast growth factor 1 (commonly known as FGF-1) , ras homolog family member U (commonly known as RHOU) , and thymidine phosphorylase (commonly known as TYMP) genes are associated with low hepatic differentiation[ 17 ], which can be used to predict the differentiation potential in early EB. Therefore, EB-based differentiation systems not only help to increase the percentage of target cells, but also contribute to the prediction of differentiation potentials in the early stage, which improves efficiency directly and indirectly, respectively.…”
Section: Differentiation Induction From Hpscsmentioning
confidence: 99%
“…hPSCs expressing the highest levels of SALL3 mRNA tend to differentiate into the most ectodermal system, while cells expressing the lowest levels of SALL3 mRNA tend to differentiate into the most mesodermal or endodermal cell types. Specifically, three genes, FGF-1 , RHOU , and TYMP , were selected as predictors of hepatic differentiation, with low prediction scores linked to low hepatic diffe-rentiation[33].…”
Section: Introductionmentioning
confidence: 99%